Barriers and facilitators of patient centered care for immigrant and refugee women: a scoping review - Tali Filler; Bismah Jameel; Anna R. Gagliardi (BMC, 2020)
Abstract Background Migrants experience disparities in healthcare quality, in particular women migrants. Despite international calls to improve healthcare quality for migrants, little research has addressed this problem. Patient-centred care (PCC) is a proven approach for improving patient experiences and outcomes. This study reviewed published research on PCC for migrants. Methods We conducted a scoping review by searching MEDLINE, CINAHL, SCOPUS, EMBASE and the Cochrane Library for English-language qualitative or quantitative studies published from 2010 to June 2019 for studies that assessed PCC for adult immigrants or refugees. We tabulated study characteristics and findings, and mapped findings to a 6-domain PCC framework. Results We identified 581 unique studies, excluded 538 titles/abstracts, and included 16 of 43 full-text articles reviewed. Most (87.5%) studies were qualitative involving a median of 22 participants (range 10-60). Eight (50.0%) studies involved clinicians only, 6 (37.5%) patients only, and 2 (12.5%) both patients and clinicians. Studies pertained to migrants from 19 countries of origin. No studies evaluated strategies or interventions aimed at either migrants or clinicians to improve PCC. Eleven (68.8%) studies reported barriers of PCC at the patient (i.e. language), clinician (i.e. lack of training) and organization/system level (i.e. lack of interpreters). Ten (62.5%) studies reported facilitators, largely at the clinician level (i.e. establish rapport, take extra time to communicate). Five (31.3%) studies focused on women, thus we identified few barriers (i.e. clinicians dismissed their concerns) and facilitators (i.e. women clinicians) specific to PCC for migrant women. Mapping of facilitators to the PCC framework revealed that most pertained to 2 domains: fostering a healing relationship and exchanging information. Few facilitators mapped to the remaining 4 domains: address emotions/concerns, manage uncertainty, make decisions, and enable self-management. Conclusions While few studies were included, they revealed numerous barriers of PCC at the patient, clinician and organization/system level for immigrants and refugees from a wide range of countries of origin. The few facilitators identified pertained largely to 2 PCC domains, thereby identifying gaps in knowledge of how to achieve PCC in 4 domains, and an overall paucity of knowledge on how to achieve PCC for migrant women.